Temporal trend of mortality by suicide among adults in Brazil: 2000 to 2015 - Duarte, Sasckia Kadishari Medeiros (Trends Psychiatry Psychother, 2021)
OBJECTIVE: To analyze temporal trends of mortality due to suicide among adults in Brazil, by macroregion and gender, from 2000 to 2015. METHODS: A retrospective study of temporal trends in suicide mortality rates in adults aged 20 to 64 years, by macroregion and gender, from 2000 to 2015. Data from the Brazilian Mortality Database (SIM) and from the Brazilian Institute of Geography and Statistics (IBGE) were used. The mortality rate trends analysis was performed using simple linear regression, with Stata 14 software. RESULTS: There was an upward trend in mortality due to intentionally inflicted self-harm in the Brazilian adult population in the North, Northeast, and Southeast regions for both genders (p<0.001), with predominance in the male population in these three regions and throughout the country (p<0.001). A downward trend was observed in the South and Midwest (p=0.003 and p=0.040). CONCLUSION: Mortality due to intentionally inflicted self-harm has increased in Brazil, but has undergone important variations in different parts of the country. Even a regional analysis is insufficient to achieve a thorough evaluation of these contrasts because of the country’s continental proportions and data collection biases. Further studies focused on this topic are required.